(untitled) (Discourse of Law and Administration, 2023)
The concept of community in the framework of the administrative law is used as a notion of a tool, however, as a part of this study is used as a notion of the subject. Community as a subject formed by natural persons takes various forms and can be examined from different perspectives. These studies must take into account the realistic aspect of community and its abstract nature. The essence of the analyzed notion is related to its values, in frames of which solidarity and responsibility should be distinguished. Without solidarity of people forming community as well as without the responsibility of its members for the community, there is no community. The concept in question was used on the base of local self-government by introducing the concept of self-government (either local or regional) into the act on municipal self-government. This concept covers the inhabitants of the community and they form the community from the provision of the law. One can either join or leave the community only in accordance with the manner indicated by law. The relationships between members of community, between them and community authorities and the community itself are often standardised by legal norms.